Therapeutic Potential of Molecular Hydrogen in Metabolic Diseases from Bench to Bedside - Fei Xie; Yifei Song; Yang Yi; Xue Jiang; Shiwen Ma; Chen Ma; Junyu Li; Ziyi Zhanghuang; Mengyu Liu; Pengxiang Zhao; Xuemei Ma (MDPI AG, 2023)
Oxidative stress and chronic inflammation have been implicated in the pathophysiology of metabolic diseases, including diabetes mellitus (DM), metabolic syndrome (MS), fatty liver (FL), atherosclerosis (AS), and obesity. Molecular hydrogen (H2) has long been considered a physiologically inert gas. In the last two decades, accumulating evidence from pre-clinical and clinical studies has indicated that H2 may act as an antioxidant to exert therapeutic and preventive effects on various disorders, including metabolic diseases. However, the mechanisms underlying the action of H2 remain unclear. The purpose of this review was to (1) provide an overview of the current research on the potential effects of H2 on metabolic diseases; (2) discuss the possible mechanisms underlying these effects, including the canonical anti-oxidative, anti-inflammatory, and anti-apoptotic effects, as well as suppression of ER stress, activation of autophagy, improvement of mitochondrial function, regulation of gut microbiota, and other possible mechanisms. The potential target molecules of H2 will also be discussed. With more high-quality clinical trials and in-depth mechanism research, it is believed that H2 will eventually be applied to clinical practice in the future, to benefit more patients with metabolic disease.